Resource recovery and wastewater treatment modelling. Issue 4 (7th March 2019) - Solon, Kimberly; Volcke, Eveline I. P.; Spérandio, Mathieu; van Loosdrecht, Mark C. M.
Abstract : This paper discusses the extent to which new unit processes applied for resource recovery can be modelled with conventional ASMs, the additional modelling challenges being faced, while providing recommendations on how to address current modelling research gaps. Abstract : Traditional wastewater treatment plants (WWTPs) are increasingly regarded as water resource recovery facilities (WRRFs), reflecting the value of water, nutrients, energy and other resources, besides ensuring the required effluent quality. Resource recovery techniques involve biochemical, physical and physico-chemical processes, and even previously unexploited biological conversions. Biopolymer and bioplastic production also reveal the remarkable potential present in our microbial cultures. Models have demonstrated their usefulness to optimize WWTP operation to achieve better effluent quality at lower costs; they also constitute a useful tool to support the transition of WWTPs into WRRFs that maximize the valorization of products recovered from wastewater. In this paper, the extent to which the new techniques and unit processes applied for resource recovery could be modelled with conventional activated sludge models (ASMs) and additional modelling challenges being faced are discussed while providing recommendations of potential approaches to address current modelling research gaps.